Biomarkers in stable coronary artery disease - Rusnak, Jonas; Fastner, Christian; Behnes, Michael; Borggrefe, Martin; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: Coronary Artery Disease (CAD) is the most common reason for death in the western hemisphere. Therefore, a well-functioning risk-management has been established over the past decades with uprising interest in ‘novel’ biomarkers to predict adverse coronary events and detect patients with subclinical CAD. This review will focus on selected biomarkers belonging to the family of inflammatory markers (fibrinogen or hs-CRP) or to the family of lipid-associated markers (Lipoprotein associated PA2 or Lipoprotein a) and organ-specific biomarkers (hs-troponin, Cystatin C or NTproBNP). Methods: This review is based on a pubmed search focusing on the biomarkers fibrinogen, hs-CRP, Lipoprotein associated PA2, Lipoprotein a, hs-troponin, NT-proBNP and Cystatin C. Results: The search retrieved 149 references containing meta-analysis, prospective and retrospective studies concerning the usage of the selected biomarkers in risk prediction and detection of CAD. Despite clinical studies, current guidelines of the European Society of Cardiology (ESC), the American Heart Association (AHA) and the Canadian Cardiovascular Society (CCS) were analyzed regarding their recommendation of the implementation of biomarkers in clinical routine. The review identified promising stand-alone biomarkers and multi-marker risk models for CAD patients. Conclusion: Novel biomarkers detect patients at risk beyond established risk scores. However, an ideal biomarker fulfilling all necessary criteria does still not exist.